Cost-Benefit Analysis of Proposed California Oil and Gas Refinery Regulations - Gonzales, Daniel (RAND Corporation, 2016)
The research reported here assessed the costs and benefits of the proposed California process safety management (PSM) and California Accidental Release Prevention regulations that are designed to improve safety at oil and gas refineries operating in California. The authors estimate these costs and benefits in four categories: costs to industry, costs to society, benefits to industry, and benefits to society.